Stunting severity and developmental outcomes in early childhood in Central Java, Indonesia - Santosa, Qodri; Hapsari, Ariadne Tiara; Agustina, Nenden Nursyamsi; Oliviany, Windy; Roestijawati, Nendyah; Muntafiah, Alfi (Indonesian Pediatric Society, 2025)
Background Stunting in early childhood remains a critical global health issue, particularly in low- and middle-income countries such as Indonesia. Defined by height-for-age below -2 standard deviations from the WHO growth standards, stunting indicates chronic malnutrition and is linked to impaired developmental outcomes, including cognitive and motor delays. Objective To elucidate the specific areas of development most affected by stunting and to identify potential sociodemographic and health-related factors that may contribute to the observed developmental disparities among these children. Methods A cross-sectional comparative study was conducted in Central Java, Indonesia, involving 144 stunted children. Stunting severity was categorized as stunted or severely stunted. Standardized anthropometric measurements and developmental assessments using the Denver II tool were performed, focusing on four domains: personal-social interaction, fine motor skills, language acquisition, and gross motor skills. Data were analyzed using the Mann-Whitney and Chi-square tests with a significance level of P < 0.05. Results Children in the severely stunted group exhibited a significantly higher prevalence of fine motor delays compared to the stunted group (17.0% vs. 4.1%, respectively; P=0.013). No significant differences were observed in other developmental areas. Sociodemographic and health factors were comparable across both groups. Conclusion Severe stunting is significantly associated with delayed fine motor development. Furthermore, as sociodemographic and health factors are comparable across groups, these findings underscore the urgency of implementing targeted nutritional interventions and routine developmental monitoring to mitigate the adverse effects of stunting on early childhood growth and development.